Evaluation of cereal-legume intercropped forages for smallholder dairy production in Zimbabwe - Ngongoni, N. T.; Mwale, M.; Mapiye, C.; Moyo, M. T.; Hamudikuwanda, H.; Titterton, M. (Fundación CIPAV, 2021)
A study was conducted at Henderson Research Station in Mazoe, Zimbabwe to assess the establishment, persistence, yield and nutritive quality of cereal and ley legumes sole crops and cereal-legume intercrops on sandy and clay soils. Four cereals, maize and three sorghum varieties; Jumbo, Pan 888 and Sugargraze, and five legume varieties Vigna unguiculata, (Cow pea) Lablab pupureus (Lablab), Crotolaria juncea (Sunnhemp), Glycine max (Soyabean) and Lupinus albus (Lupin) were used. A 2 x 4 x 5 factorial experiment in a split-split plot design with soil type as the main plot factor, cereal as the sub-plot factor and legume as sub-sub-plot factor was used.